1992
DOI: 10.1210/endo.131.4.1396324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium deficiency on thyroid hormone economy in rats.

Abstract: In selenium-deficient rats, peripheral T4 to T3 conversion is markedly decreased due to the loss of the selenoprotein, type I iodothyronine 5'-deiodinase (5'D-I). Despite the marked increase in circulating T4 that results from this loss of 5'D-I, serum T3 concentrations in selenium-deficient rats remain in the normal range. To determine the physiological mechanism(s) that maintains circulating T3 when peripheral T4 to T3 conversion is impaired, we examined the interrelationships between selenium intake and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…Intrathyroidal 5'D-I deiodination of T4 to generate T3 does not appear to be a major source of circulating T3, because serum T3 concentrations were not decreased in the ATU-treated rats despite a 60% reduction in 5'D-I activity. However, Laurberg has reported that intrathyroid deiodination of T4 to T3 accounts for a considerable portion of the T3 secreted from the dog thyroid (26, 27) and we have also suggested that this pathway of T3 generation in the thyroid appears to be important in the rat (23).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Intrathyroidal 5'D-I deiodination of T4 to generate T3 does not appear to be a major source of circulating T3, because serum T3 concentrations were not decreased in the ATU-treated rats despite a 60% reduction in 5'D-I activity. However, Laurberg has reported that intrathyroid deiodination of T4 to T3 accounts for a considerable portion of the T3 secreted from the dog thyroid (26, 27) and we have also suggested that this pathway of T3 generation in the thyroid appears to be important in the rat (23).…”
Section: Discussionsupporting
confidence: 56%
“…It has been shown previously that a marked decrease in 5'D-I activity in the liver and kidney by more than 90% in selenium-deficient intact rats was associated with only a modest or no decrease in the serum T3 concentration (20)(21)(22). fn addition, in selenium-deficient, thyroidectomized, T4-replaced rats the serum T3 concentration was only decreased by 20% as compared to selenium-supplemented, thyroidecto¬ mized, T4-replaced rats (23). These data are consistent with the finding that in mice lacking 5'D-I, the serum T3 concentration is normal (24,25).…”
Section: Discussionmentioning
confidence: 85%
“…We therefore looked for the effect of reduced food intake in a separate experiment, and showed that the decrease in serum T3 and T4 after 24-h starvation was not affected by depleting the liver of Kupffer cells. Considering that considerable amounts of T3 are produced from deiodination of T4 in the thyroid, which appears to be an important source of T3 production in rats (36), it might be plausible that decreased levels of thyroidal 5'-deiodinase contribution to the observed LPS-induced decrease of serum T3. This is in agreement with the results of O'Mara et al, who found only a significant decrease in 5'-deiodinase mRNA in rats after 48-h starvation but not after 24 h, while serum T3 was already signifi¬ cantly decreased (34).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with data obtained from animal studies. Prolonged, isolated selenium deficiency in rodents causes an almost complete loss in liver 5 DI activity and an increase in circulating T 4 [23] and T 4 half-life with no [11,23] or little [10,24] changes in T 3 or TSH concentrations. Interestingly, selenium deficiency is associated with an increase in serum rT 3 concentrations in young rats [25] but not in adult male [9,10] or non-pregnant female rats [26].…”
Section: Isolated Selenium Deficiencymentioning
confidence: 99%
“…5 DI contains the rare aminoacid selenocysteine [8] and tissue content of 5 DI is proportional to selenium intake. In rodents, severe selenium deficiency causes a marked decrease in liver and kidney 5 DI activities [9][10][11]. The other isozyme, type II 5 -deiodinase (5 DII), is abundant in human brain, heart, skeletal muscle [12], pituitary tumors [13] and thyroid [12,14] (rev in [7]).…”
Section: Introductionmentioning
confidence: 99%